Receptor de angiotensina II envolvido na regulação da maturação nuclear de oócito bovino - Benetti, Luciana (2008)
The aim of this study was to verify the type of angiotensin II (AngII) receptor involved in nuclear maturation of bovine oocytes and the possible participation of bradykinin (BK) as a mediator of AngII in this process. The first experiment was conducted to analyze the type of AngII receptor, for this cumulus-oocyte complexes (COCs) were cultured for 7 or 12h in the presence of follicular hemisections and AngII (10-11M), with or without the antagonists losartan (10-6M; selective for AT1 receptor), PD123319 (10-6M; selective for AT2 receptor) or saralasin (10-7M; AT1 and AT2 antagonist). Additionally, two control groups were used where the oocytes were cultivated in the absence or presence of follicular hemisections (positive and negative control, respectively). Oocytes cultured for 7h in the presence AngII reached 70,4% germinal vesicle breakdown (GVBD). When losartan was added to the maturation medium with AngII, the GVBD oocytes did not have any difference (73,2%), however when COCs were cultured in the presence of AngII + PD123319, the nuclear maturation was lower (52,1%; P<0,05). The cultivation of the oocytes for a larger period (12h) did not cause a significant difference in relation to those 7h treatments (P<0,05). These data indicate that the AT2 receptor mediate the actions of AngII during the nuclear maturation in bovine. In a second experiment, the effect of different concentrations of PD123319 was verified in the oocytes nuclear maturation in the presence of AngII (10-11M) and follicular hemisections. The culture was accomplished by 7h in a similar experimental design as previous experiment and it was verified that the inhibition induced by the antagonist happened in a dose-dependent way and there is lineal relation between concentration of PD and rates of obtained RVG (P=0,0306). To verify the participation of BK in the action mechanism of AT2 receptors, the oocytes were cultured in the presence of AngII (10-11M) and follicular hemisections with or without Hoe-140 (antagonist of B2 receptors of BK) in different concentrations (10-6, 10-7, 10-8 and 10-9M) for 7h. In this experiment, there was not any difference in the rates of GVBD oocytes among the groups treated with the antagonist and the AngII group (P>0,05). These data allow to infer that AngII acts in the nuclear maturation of the bovines oocytes activating the AT2 receptors and that the BK/receptor B2 pathway is not involved in that process.